Pengaruh Karakteristik CEO dan Kepemilikan Saham Manajerial terhadap Real Earnings Management pada Perusahaan Pertambangan yang Terdaftar di BEI tahun 2020-2023 - Humaira, Heryuni; Afriyenti, Mayar (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to find out how the characteristics of CEOs and managerial stock ownership affect real earnings management. In this study, the sampling method used the purposive sampling method, so that 196 research samples were obtained, from 49 mining companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. In hypothesis testing, this study used panel data regression analysis with a fixed effect model (FEM) and tested the model using EViews 12. These findings show that CEO financial expertise has a negative effect on real earnings management. Meanwhile CEO nationality, CEO tenure, CEO gender, CEO politically connected, CEO turnover, and managerial stock ownership do not have a significant effect on real earnings management.